Analisis Efektivitas Penyaluran Bantuan Program Keluarga Harapan (PKH) Dalam Meningkatkan Kesejahteraan Keluarga Di Kelurahan Kayu Putih Jakarta Timur Tahun 2021 - Linda Oktaviani; Ivan Budi Susetyo (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Poverty is a multidimensional problem characterized by the low average quality of life, education, health, children's nutrition, and drinking water sources. Various efforts have been made by the Indonesian government to alleviate poverty, one of which is through the launch of the Ideal Family Program (PKH). This study aims to describe the effectiveness of the Ideal Family Program (PKH) aid distribution in improving family welfare in the Kayu Putih Urban-Village, East Jakarta in 2021 and to find out the obstacles and efforts needed to be made to overcome them. The research method used was descriptive qualitative method. The results of the study show that Ideal Family Program (PKH) or Ideal Family Program in Kelurahan Kayu Putih, East Jakarta in 2021 has been running effectively but not yet optimal because there are still indicators that have not been fulfilled. Obstacles in distributing PKH assistance in Kelurahan Kayu Putih included delays in fund disbursment, difficulty in scheduling monthly group meetings, and PKH participants' delays in submitting documents. To overcome these problems, it is necessary for the Social Welfare Data and Information Center of the Ministry of Social Affairs and the Implementation Unit for the Ideal Family Program to have a good coordination, from the center to the local level as well as the channeling banks regarding the disbursement of funds. The PKH facilitator must explain that attending the Family Capacity Building Meeting (P2K2) is a form of commitment and obligation of PKH participants. PKH implementers must also provide the necessary systems for monitoring the Ideal Family Program (PKH).